LEGAL ANALYSIS OF THE IMPLEMENTATION OF SHARIA BANKING LAW AND COMPILATION OF SHARIA ECONOMIC LAW IN STRENGTHENING THE NATIONAL FINANCIAL SYSTEM IN INDONESIA - Gunawan Widjaja; Siti Nur Azizah (Adisam Publisher, 2025)
This study conducts a legal analysis of the implementation of the Islamic Banking Law and the Compilation of Islamic Economic Law in efforts to strengthen the national financial system in Indonesia. Using a literature review method, the study evaluates the legal and regulatory aspects governing Islamic banking, as well as the role of the Compilation of Islamic Economic Law as a normative foundation in Islamic economic practices. The results of the study indicate that the Islamic Banking Law provides a solid legal framework for the operation of Islamic banking in accordance with Islamic principles, while the Compilation of Islamic Economic Law serves as a legal guideline for religious courts and Islamic financial institutions in resolving disputes and regulating Islamic economic transactions. The integration and strengthening of the implementation of these two legal instruments have the potential to enhance stability, inclusion, and justice in the national financial system. However, efforts to improve regulations and adapt to economic and technological developments must continue to ensure that the role of Islamic finance in national development can be maximised sustainably.